EFFICIENT USE OF TOURIST RESOURCES IN DEVELOPING TOURISM IN THE REGION (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article provides information and recommendations on the role of tourism resources in the development of tourism in Uzbekistan and their contribution to tourism.
Keywords: agrotourism, tourist resource, agrotourism product, agrotourism destination.